2020
DOI: 10.51643/22562915.19
|View full text |Cite
|
Sign up to set email alerts
|

Relación neutrófilos-linfocitos en tumores sólidos.

Abstract: Introducción: la asociación entre el cáncer y la inflamación ha despertado gran interés en los últimos años. La relación neutrófilos/linfocitos (NLR) se ha utilizado como valor pronóstico y de desenlace clínico en cáncer. Objetivo: determinar la NLR elevada (>2,5) con el estadio clínico, metástasis y demás marcadores de severidad en pacientes con tumores sólidos. Materiales y métodos: estudio transversal analítico, incluyendo 170 historias clínicas de pacientes con tumores sólidos, no expuestos a quimiotera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…On the other hand, in tumors, neoplastic cells, normal cells and inflammatory cells constitute a tumor immune or inflammatory microenvironment (11) which, under certain stimuli, modulates the immune response and modifies its biologic conditions, favoring increased vascular permeability, angiogenesis, cell proliferation and mobilization, thus stimulating tumor growth and distant spread (10). This is how some authors have reported an association between these inflammatory markers and poor prognosis or advanced stages of the disease (7,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in tumors, neoplastic cells, normal cells and inflammatory cells constitute a tumor immune or inflammatory microenvironment (11) which, under certain stimuli, modulates the immune response and modifies its biologic conditions, favoring increased vascular permeability, angiogenesis, cell proliferation and mobilization, thus stimulating tumor growth and distant spread (10). This is how some authors have reported an association between these inflammatory markers and poor prognosis or advanced stages of the disease (7,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, en los tumores, las células neoplásicas, las células normales y las células inflamatorias constituyen un microambiente inmune o inflamatorio tumoral 11 que, bajo determinados estímulos, modula la respuesta inmune y modifica sus condiciones biológicas, lo que facilita una mayor permeabilidad vascular, la angiogénesis y la proliferación y movilización celular, estimulando su crecimiento y diseminación a distancia 10 . De esta manera, algunos autores han informado una asociación de estos marcadores inflamatorios con un mal pronóstico o fases avanzadas de la enfermedad 7 , 12 - 17 .…”
Section: Introductionunclassified